A novel ablation strategy of premature ventricular contractions originating from summit guided by CartoUNIVU module. Issue 9 (19th May 2020) - Li, Xuexun; Li, Jianping; Chu, Hongxia; Liu, Xingpeng
Abstract: Background: Premature ventricular contractions (PVCs) from left ventricular (LV) summit remain challenging for the risk of coronary artery injury. Computed tomographic or intracardiac echocardiography may be helpful, but both still have many limitations. CartoUNIVU module has rarely been used in PVC ablation. Methods: A total of 22 patients (14 men: mean age 56.4 ± 13.3 years) with an electrocardiogram indication of summit PVCs were included in the two centers study. A novel strategy ablation with the Image Integration Module CartoUNIVUTM module was performed for all the patients with PVCs originating from LV summit area, especially to prevent the coronary artery injury. Results: The procedure time was 78.6 ± 22.7 minutes, and the fluoroscopy time was 12.5 ± 3.1 minutes. The distance between the target and nearest coronary artery was 8.0 ± 3.1 mm. Three patients with the distance to the nearest coronary artery <5 mm. During a mean follow‐up of 11.0 ± 1.7 months, 21/22 (95.5%) patients were free from clinical PVC. No coronary artery injury was detected in the all the ablation procedures. Conclusion: The novel strategy ablation with the Image Integration Module CartoUNIVU module is safe and effective for PVCs originating from LV summit area, especially to prevent the coronary artery injury.